To simplify this expression, we need to use the multiplication rule and division rule for logarithms:

`ln(x/{x-8})+ln({x+8}/x)-ln(x^2-64)` combine + terms with multiplication

`=ln({x(x+8)}/{(x-8)x})-ln((x-8)(x+8))` cancel common factors

`=ln({x+8}/{x-8})-ln((x-8)(x+8))` combine - terms with division

`=ln({(x+8)}/{(x-8)(x-8)(x+8)})` cancel common factors

`=ln(1/(x-8)^2)` write as negative exponent

`=ln(x-8)^{-2}` use power rule

`=-2ln(x-8)`

**The expression simplifies to `-2ln(x-8)` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now